2018
DOI: 10.1002/ca.23079
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the male inferior hypogastric plexus: What should we know for nerve sparing surgery

Abstract: The aim of this study was to investigate the nerve supply to the structures in the male lesser pelvis and review its clinical relevance, especially during nerve sparing surgery. Three formalin-embalmed and 16 Thiel-embalmed male hemipelves were used. They were microdissected after repeated treatments with nitric acid diluted 1:10 with milliQ-water. The inferior hypogastric plexus (IHP) is a fan-like structure lateral from the rectum on the fascia of the levator ani. Nerves emerging from the proximal, solid par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…A study on the EUS reported that it is difficult to analyze because its overall shape is unclear due to growth of the prostate and the invasion of the prostatic vascular plexuses, and that the textbook descriptions are inconsistent 7 . Although the term "sphincter" is reminiscent of a circular muscle, it has been reported that the EUS is horseshoe-shaped rather than perfectly circular 9,22,23 . Our group clarified that horseshoe-shaped EUS is not an independent muscle, but is formed from partial muscle bundles of the EAS, STP, and LA so it is continuous with the surrounding pelvic floor muscles 12 .…”
Section: Discussionmentioning
confidence: 99%
“…A study on the EUS reported that it is difficult to analyze because its overall shape is unclear due to growth of the prostate and the invasion of the prostatic vascular plexuses, and that the textbook descriptions are inconsistent 7 . Although the term "sphincter" is reminiscent of a circular muscle, it has been reported that the EUS is horseshoe-shaped rather than perfectly circular 9,22,23 . Our group clarified that horseshoe-shaped EUS is not an independent muscle, but is formed from partial muscle bundles of the EAS, STP, and LA so it is continuous with the surrounding pelvic floor muscles 12 .…”
Section: Discussionmentioning
confidence: 99%
“…This might be because the hypogastric nerve fibers, which run along the tip of the SV, can be spared more extensively with the SVS approach as compared to the NS approach. 3,30 Therefore, in order to optimize urinary continence, we always aim at sparing the SV if it is safe from an oncological standpoint; this is the reason we perform SVS in some patients even with decreased erectile function preoperatively. Hence, although baseline sexual function clearly plays an important role in the decision whether the aim should be SVS, it is not the only variable we take into account.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a connection between the two parts was demonstrated in approximately one third of the samples investigated. This could explain the significantly better recovery of continence after pelvic surgery 30 .…”
Section: A C C E P T E D U N E D I T E D M a N U S C R I P Tmentioning
confidence: 92%
See 1 more Smart Citation
“…In sum, our findings elucidate ectopic sympathetic neurons in the ventral root of the human spinal cord. Such findings are important for better understanding of the variations of the human nervous system [30][31][32][33].…”
Section: Clinical Relevancementioning
confidence: 96%